Exploring Teachers' Utilization of Adaptive Learning Platform Features to Foster Students' Self-Regulated Learning: A Focus on ALEKS Platform - ALMASRI, TASNEEM “MOHAMMED NOOR” (2024)
Adaptive Learning (AL) is a revolutionary promising technology that employs artificial intelligence to optimize students’ performance and attainment by providing customized learning frameworks that cater to each learner's unique needs. However, the isolated nature of this learning environment has not only necessitated ensuring that students are equipped with the essential skills to thrive within this landscape but also underscored the importance of aligning teachers’ practices to meet this demand. Cultivating students’ Self-regulated learning (SRL) is a critical practice that is needed in this academic setting. A scarcity of studies that explore teachers’ utilization of Adaptive Learning Platforms (ALP) to foster students’ academic competencies, including SRL, was noticeable. Focusing on ALEKS, this study investigates teachers' perceptions of the effectiveness of ALEKS’s features in promoting students' SRL skills. Additionally, the study seeks to assess teachers’ employment of ALEKS’s tools to enhance students’ SRL. Thirdly, this study explores how ALEKS's features could enhance students' SRL. A parallel mixed-method approach was adopted to address the research questions: an online questionnaire and semi-structured interviews. The findings revealed a general affirmation among teachers of ALEKS’s capacity to promote students’ SRL. Moreover, the findings showcased the presence of teachers’ employment of strategies that are believed to foster students' SRL skills within ALEKS context and underlined the need for more consistent engagement. Furthermore, the findings, combined with the theoretical framework, demonstrated ALEKS’s SRL promotion potential. The results additionally highlight obstacles to using ALEKS or other ALPs, and shed light on valuable implications for educators, policymakers, and instructional designers.